HCV-specific lymphocyte responses in individuals with positive anti-HCV but negative HCV-RNA - SİLİ, ULUHAN (ELSEVIER SCIENCE BV, 2015)
Background: Hepatitis C virus (HCV) status cannot be reliably predicted in anti-HCV positive/HCV-RNA negative individuals who may either have recovered spontaneously or have a false-positive test due to antibody cross-reaction. Investigating T lymphocyte responses in individuals with different HCV status may help understand the cellular immune mechanisms underlying spontaneous recovery, treatment response, and chronicity. Objective: We aimed to determine whether anti-HCV positive, HCV-RNA negative individuals are truly spontaneous recoverers from acute HCV infection. Study design: We used enzyme-linked immunosorbent spot (ELISPOT) assay to compare HCV-specific lymphocyte response among anti-HCV positive/HCV-RNA negative individuals, patients with sustained virological response to interferon-gamma/ribavirin treatment, and patients with chronic HCV infection. Results: We found that 83% of anti-HCV positive/HCV-RNA negative individuals without a past medical history of acute icteric hepatitis had an HCV-specific T lymphocyte response in peripheral blood. Lymphocyte responses in these individuals were similar in magnitude to treatment responders unlike patients with chronic HCV whose virus-directed immunity was significantly suppressed. Conclusions: Detection of HCV-specific T lymphocyte responses using ELISPOT is a feasible method to ascertain past asymptomatic acute HCV infection. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: HCV; T-lymphocyte; Spontaneous recovery; ELISPOT; False-positive serology; HEPATITIS-C-VIRUS; IMMUNE-RESPONSES; THERAPY; INFECTION